Recuperación de cárcavas con agave (penco azul) para la protección biológica ambiental del estadio Ceypsa, parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi - Corrales Freire, Carla Katherine (2013)
This research was conducted at the Technical University of Cotopaxi in its experimental center located in Salache CEYPSA, 7 kilometers from the Latacunga city of. The work began with the ground reconnaissance. It was very important to delimit using a GPS. The recovery of the gully took place with the technique of Level in A, following the contours. It was done with the aim of recovering this area and preventing further erosion existing in the sector as well as the landslides of this hill. Once the ground reconnaissance was done, we proceeded to trace the contour with the help of the A, pointing each of the curves with some stakes. It helped us to make the hollow in a better way. This hollow size is about 40x40cm each hole. Then, Each hole was filled in with the same substrate. The next step was to place the agave plants in order to plant them. Therefore we used the Inductive- Deductive and historical methods and the observation technique. The , materials used were: Laptop, Printer, Flash Memory, camera, field book, pencil, books, journals, theses, charts and tables….